2019
DOI: 10.1021/acs.oprd.9b00125
|View full text |Cite
|
Sign up to set email alerts
|

Development and Scale-Up of a Continuous Aerobic Oxidative Chan–Lam Coupling

Abstract: Despite the benefits of high atom economy and low cost, aerobic oxidations have found limited use in the synthesis of active pharmaceutical ingredients (APIs) because of safety concerns and poor selectivity. In this report, the design, development, and scale-up of a continuous, high pressure aerobic oxidation to produce the penultimate of an API are described. The identification of robust homogeneous conditions for the oxidative C−N coupling of interest and the use of diluted air allowed for the process to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Our literature review indicated the predominant use of copper(II) acetate (up to 1.5 eq. to substrate) for the CEL couplings in the earlier works . To test the analytical procedure, a model reaction was performed using catalytic amounts of the Cu(OAc) 2 ⋅ H 2 O.…”
Section: Resultsmentioning
confidence: 99%
“…Our literature review indicated the predominant use of copper(II) acetate (up to 1.5 eq. to substrate) for the CEL couplings in the earlier works . To test the analytical procedure, a model reaction was performed using catalytic amounts of the Cu(OAc) 2 ⋅ H 2 O.…”
Section: Resultsmentioning
confidence: 99%
“…Safety concerns and poor selectivity from aerobic oxidations mean that despite the benefits of high atom economy and low cost, there are limited examples in the synthesis of APIs. The development and scale-up of a continuous aerobic oxidative Chan–Lam coupling has been recently reported to produce the penultimate precursor of a pyrazole-derived API . The identification of robust homogeneous conditions for the oxidative C–N coupling of interest and the use of diluted air allowed for the continuous process to be implemented at manufacturing scale with improved safety and selectivity using a vertical “pipes-in-series” reactor.…”
Section: Overcoming the Challengesmentioning
confidence: 99%
“…Reactions that form challenging C–X bonds, including C–N, C–F, C–O, and C–CF 3 , are critically important for the discovery and design of drug-related molecules. , These coupling reactions have long relied on the judicious design of ligands that accelerate rates of reductive elimination from organometallic intermediates. Recent approaches leverage the reactivity of high-valent organometallic complexes bearing inexpensive ligands to effect similar reactions. However, accessing these high-valent organometallic complexes typically requires oxidation with superstoichiometric quantities of peroxides, , N -fluoropyridiniums, , xenon difluoride, , silver salts, hypervalent iodide, or pressurized oxygen. , Efforts to mitigate the hazards and wastes associated with strong chemical oxidants have focused on new strategies for electron transfer (ET) and oxidation, including photoredox catalysis and electrosynthesis. Electrochemistry is particularly well-suited for net oxidative (or reductive) organic transformations because reactions can be designed for the anode while providing a benign reagent, like a proton, for consumption at the opposite electrode. In doing so, electrical energy and a proton can replace energetic chemical oxidants …”
Section: Introductionmentioning
confidence: 99%
“…Application of a mediator-assisted strategy toward the development of an electrochemical Chan–Lam coupling reaction addresses the long-standing challenge of eliminating oxygen or peroxide additives from this important transformation. , ,, The requirement for hazardous oxidants has precluded the use of Chan–Lam couplings on a large scale, despite their ubiquitous application in drug discovery and small-scale synthesis. , The limited scale on which Chan–Lam reactions are currently performed is particularly frustrating because the reactions offer an easily accessible approach to forming important C–N bonds with an inexpensive copper salt as catalyst and abundant substrates. As such, this work represents not only a rare example of electrocatalysis with simple copper salts in an undivided cell but alsoto the best of our knowledgethe first example of Chan–Lam coupling to forge C–N bonds in the absence of a stoichiometric oxidant.…”
Section: Introductionmentioning
confidence: 99%